EFFECT OF PLATE THICKNESS AND ROLL GAP ON THE GEOMETRIC QUALITY OF ROLLING PRODUCTS - Hendra Hendra; Ahmad Fauzan; Zuliantoni Zuliantoni; Aswata Aswata; Kurnia Nugraha; Hermiyetti Hermiyetti; Hernadewita Hernadewita (Trends in Mechanical Engineering Research, 2023)
The gacorslot folding gate is a middle frame flanked by cross bars on the back of the shop door which has a higher level of strength than the body of the door and has better security. The U folding profile is made by a plastic deformation rolling process in which the plate is passed between the pressing roll and the sliding roll. Flat plates are used from the base material of metal plates with varying plate thickness where the metal forming process uses a cold working process. Factors that affect the results of rolling are roll dimensions, machine capacity, roll pressure lever settings and others. The thickness of the plate that can be rolled by the machine, the amount of force exerted on the roll gap, the evenness of the roll surface both vertically and horizontally and the alignment of the roll gap. The thicker the material with a large pressure spacing can affect the forming process so that it enlarges the largest angular deviation of 0.761 mm at a pressure spacing of 0.0 mm. A thicker material with a large pitch can enlarge the wing opening so that both wings bend imperfectly making the height deviation increase by 18.58 mm at a pitch of 0.0 mm. Thinner material with a large press distance at the start of the roll affects the flange width so that the rolling force exerted on the contact gap between the roll and the workpiece side is unbalanced. Get the largest size b- (8.030 mm) 0.0 mm pressure distance and b+ (7.843) 0.15 mm pressure distance.